2004
DOI: 10.1029/2004jf000119
|View full text |Cite
|
Sign up to set email alerts
|

Saving Venice by seawater

Abstract: [1] The frequency of flooding in Venice has drastically increased over the last 50 years as a major consequence of natural and anthropogenic land subsidence, mean sea level rise, and a more active lagoon hydrodynamics induced partly by deepening of the largest navigation channels. Subsurface fluid injection is a well-established technology that is currently used either to enhance oil recovery from oil fields or to reduce land settlement due to hydrocarbon production. To help mitigate the inundation events in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…In an interview released by Courier-Mail World News, an Australian newspaper, a few days later [Falconi, 2005], Jamiolkowski updated his estimate and suggested that 15 centimeters of anthropogenic uplift could be possible. Although this is a smaller amount than that predicted by Comerlati et al [2003Comerlati et al [ , 2004, it is 3 times Jamiolkowski's original estimate, and a 15-centimeter heave would be of great practical interest for Venice.…”
Section: Current Status Of the Projectmentioning
confidence: 51%
See 2 more Smart Citations
“…In an interview released by Courier-Mail World News, an Australian newspaper, a few days later [Falconi, 2005], Jamiolkowski updated his estimate and suggested that 15 centimeters of anthropogenic uplift could be possible. Although this is a smaller amount than that predicted by Comerlati et al [2003Comerlati et al [ , 2004, it is 3 times Jamiolkowski's original estimate, and a 15-centimeter heave would be of great practical interest for Venice.…”
Section: Current Status Of the Projectmentioning
confidence: 51%
“…In contrast, Jamiolkowski, also one of the chief consultants to CVN (the consortium of enterprises mandated by the Italian government to fund all the investigations and interventions fi nalized to protect Venice from the acqua alta, including the design and construction of MOSE), concluded that any in situ experimentation is premature, and he argued that the injection project would yield an uplift of only a few centimeters. On the basis of his own experience with shallow soils, Jamiolkowski assumed, without any fi eld evidence, an injected formation 5 times stiffer than the one addressed by Comerlati et al [2003Comerlati et al [ , 2004, thus implying a proportionally reduced uplift (5-6 centimeters). Comerlati et al [2003Comerlati et al [ , 2004 used data derived from actual measurements of deep in situ rock compaction and expansion performed with the aid of the marker technique [Baú et al, 2002], a consolidated approach implemented in the petroleum fi eld by major service companies such as Schlumberger and Western Atlas.…”
Section: Current Status Of the Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations of the injection process (Comerlati et al 2004) suggest that the pore pressure would increase by approximately Dp = 1.2 MPa in 10 years. Values cited above indicate an expected displacement of 24 cm, according to equation (1.1), consistent with the uplift of 10-40 cm resulting from detailed finite-element analyses (Comerlati et al 2004). Therefore, the total displacement achieved using the poroelastic effect is probably limited to fractions of a metre for reasonable combinations of variables in equation (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to raising Venice is based on the poroelastic effect produced by the subsurface injection of sea water (Comerlati et al 2004;Castelletto et al 2008). Vertical displacement resulting from an increase in pore pressure Dp is approximately…”
Section: Introductionmentioning
confidence: 99%